2022
DOI: 10.1111/gcb.16044
|View full text |Cite
|
Sign up to set email alerts
|

Animal mortality during fire

Abstract: Earth's rapidly warming climate is propelling us towards an increasingly fire-prone future. Currently, knowledge of the extent and characteristics of animal mortality rates during fire remains rudimentary, hindering our ability to predict how animal populations may be impacted in the future. To address this knowledge gap, we conducted a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 105 publications
2
76
2
Order By: Relevance
“…Our review of conservation assessments and primary literature showed that for most threatened Australian mammals, inappropriate fire regimes include high intensity and severity fires, large fire sizes and amount burned, and high-frequency fires. Intense and severe fires generate high levels of heat and smoke and increase the chances of animal mortality (Jolly et al, 2022). For example, declines of koala ( Phascolarctos cinereus ) populations have been documented following severe wildfires in forests of south-eastern Australia (Matthews et al, 2016; Phillips et al, 2021), and are probably linked to direct mortality caused by fires and reduced survival shortly after fires.…”
Section: Discussionmentioning
confidence: 99%
“…Our review of conservation assessments and primary literature showed that for most threatened Australian mammals, inappropriate fire regimes include high intensity and severity fires, large fire sizes and amount burned, and high-frequency fires. Intense and severe fires generate high levels of heat and smoke and increase the chances of animal mortality (Jolly et al, 2022). For example, declines of koala ( Phascolarctos cinereus ) populations have been documented following severe wildfires in forests of south-eastern Australia (Matthews et al, 2016; Phillips et al, 2021), and are probably linked to direct mortality caused by fires and reduced survival shortly after fires.…”
Section: Discussionmentioning
confidence: 99%
“…were more abundant in burnt compared to unburnt areas, possibly because there were fewer predators in burnt areas (Pausas et al ., 2018). Taken together, these results point to a key role of predation in shaping prey population dynamics in burnt landscapes, especially because direct mortality rates from fire are often low (Jolly et al ., 2022).…”
Section: How and Why Does Prey Vulnerability Change Post‐fire?mentioning
confidence: 99%
“…Another fruitful approach would be to conduct meta‐analyses or other quantitative syntheses focused on a specific taxonomic group, region or phenomenon (e.g. Geary et al ., 2020; Jolly et al ., 2022). Synthesis of future studies would also be aided by standardising how fires, the predator and prey guilds, and environmental context are described, so that heterogeneity between study contexts and designs can be accounted for (Geary et al ., 2020).…”
Section: Outstanding Questions and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…We chose these three commonly studied climate extremes, as their frequency is increasing at unprecedented rates and, accordingly, their effects on ecosystems are rapidly growing ( IPCC et al., 2018a ). We do acknowledge that many other climate-related extreme events are also increasing worldwide, such as more severe snow and windstorms, and fire events, and their effects on terrestrial ecosystems can be highly dramatic ( Díaz-Yáñez et al., 2019 ; Jolly et al., 2022 ). However, in this review we restrict ourselves to three major events, as many other extreme events can be related to temperature and water extremes.…”
Section: Introductionmentioning
confidence: 99%